CHARACTERIZATION OF CHITOSAN AND POLYETHYLENE GLYCOL BIOPOLYMERS COATINGS ON MAGNETIC SPINEL FeFe2O4 NANOPARTICLES - Sh. Talebniya; M. R. Saeri; I. Sharifi; A. Doostmohammadi (Journal of Advanced Materials in Engineering, 2022)
Magnetic nanoparticles are of interest in various research fields such as magnetic fluids, catalysts, biotechnology, medicine, information storage, and environmental issues. However, spinel ferrite magnetic nanoparticles with proper magnetic properties could not be used alone in these applications because of their lack of biocompatibility and instability in aqueous solutions. Surface coating is an effective strategy to eliminate or minimize this issue. In this study, FeFe2O4 and ZnFe2O4 spinel ferrites were synthesized using the reverse co-precipitation method under a nitrogen gas atmosphere. The magnetic behavior of the particles, determined by a vibrating magnetometer (VSM) showed the saturation magnet (Ms) values of the FeFe2O4 and ZnFe2O4 spinel. Fourier-transform infrared (FTIR)  spectra showed two high-frequency bands v1 and v2 at about 554-578 and 368-397 cm-1, respectively, which were related to the spinel structure. Finally, the synthesized FeFe2O4 nanoparticles were coated with chitosan and polyethylene glycol (PEG) biopolymers. The TEM and FTIR analysis indicated that the magnetic nanoparticles were uniformly coated by the biopolymers.